Analisis Perkembangan Wilayah Dengan Sektor Unggulan di Kota Surakarta Tahun 2009 - 2013 - Budiarso, Agung; , Drs. Priyono, M.Si; , Drs. H. M. Musiyam, M.T.P (2015)
ABSTRACT The population growth should be followed by sustainable economic growth, so that we need an extra income each year by increasing the Gross Regional Domestic Product. The implementation should be focused on the sectors development that have a multiplier effect which is large against other sectors or the economy as a whole. This study aims to determine the leading economy sector of Surakarta as an information substance in the economic development plan. The method used is secondary data from Gross Regional Domestic Product of Surakarta by district in 2009-2013. The analysis tool used is the analysis of Klassen Typologi, analysis of Location Quotien (LQ), analysis of Shift Share, and using Gegraphic Information System (GIS). The result of Klassen typology analysis shows the advanced and fast- growing sector, for the District of Laweyan is one sector; for the district of Serengan is two sectors; for the district of Pasarkliwon, Jebres and Banjarsari are three sectors. The result of Location Quotient analysis show the basic sectors, for the Distric of Laweyan and Jebres there are four sectors, for the district of Pasarkliwon and Serengan there are three sectors, and for the District of Banjarsari there are five sectors. The result of Shift Share analysis show the competitive sector which grows faster than the City, for the District of Laweyan and Serengan there are four sectors; for the district of Pasarkliwon there are six sectors; for the district of Jebres there are seven sectors; and for the district of Banjarsari there are five sectors. Research conclucions from the analysis of Typologi Klassen, Location Quotient, and Shift Share can be determined the potencies of leading sectors by classifying the advanced and fast-growing sectors, basic sectors, the competitive sectors which grow faster than the city, which are for the industrial sector, water gas electricity sector, communication transport sector in the district of Jebres; for the building sector in the District of Banjarsari; for the hotel and restaurant trade sector in the district of Serengan and Jebres; for the financial leasing services sectors in the District of Laweyan and Pasarkliwon; the services sectors in the District of Pasarkliwon and Banjarsari. The processing result of Geographical Information Systems produces nine potency maps of the leading sectors.